A gene for pachyonychia congenita is closely linked to the keratin gene cluster on 17q12-q21. Issue 9 (September 1994) - Munro, C S; Carter, S; Bryce, S; Hall, M; Rees, J L; Kunkeler, L; Stephenson, A; Strachan, T
Abstract : Pachyonychia congenita (PC) is a group of hereditary syndromes which have in common a hypertrophic dystrophy of the distal nail, and are associated with a variety of additional features, notably various dyskeratoses of skin and mucous membranes. The pathology is unknown but the array of clinical features suggests the possibility of a keratin abnormality. In the present report we describe linkage analyses in a large PC pedigree of the Jackson-Lawler type, a subtype which is characterised by multiple epidermal cysts, hair abnormalities, and natal teeth. The disease locus in this family was found to be tightly linked to markers mapping within, or very close to, the keratin type I cluster at 17q12-q21; maximum lod scores for linkage of the disease to a KRT10 polymorphism and to D17S800, a marker known to be very tightly linked to KRT10, were respectively +4.51 and +7.73, both at theta = 0.00. Although always likely, our findings provide strong evidence of a keratin gene anomaly underlying an inherited disorder affecting epidermis, nail, hair, and mucosa. These findings permit testing to see if pachyonychia congenita shows any locus heterogeneity and suggest specific candidate keratin genes for mutation searching studies. In addition, they suggest a role for keratins in the phenomenon of natal dentition.